THE ANALYSIS OF WASTEWATER FROM CAR WASHING STATIONS AND ITS IMPACT ON THE ENVIRONMENT (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The main pollutants in the wastewater after the plant are mainly suspended solids, surfactants and petroleum products. Given that the latter are substances that are difficult to oxidase in municipal sewage treatment plants, there is a need to treat the polluted water directly at the plant itself before discharge to the municipal sewage system. This article deals with the analysis of wastewater from car wash stations and its impact on the environment.